Neurogenic Inflammation and Cardiac Dysfunction due to Hypomagnesemia - Kramer, Jay H. (2009)
Hypomagnesemia continues to be a significant clinical disorder that is present in patients with diabetes mellitus, alcoholism, and treatment with magnesuric drugs (diuretics, cancer chemotherapy agents, etc.). To determine the role of magnesium in cardiovascular pathophysiology, we have used dietary restriction of this cation in animal models. This review has highlighted some key observations which helped formulate the hypothesis that release of substance P (SP) during experimental dietary Mg deficiency (MgD) may initiate a cascade of deleterious inflammatory, oxidative, and nitrosative events, which ultimately promote cardiomyopathy, in situ cardiac dysfunction, and myocardial intolerance to secondary stresses. SP acts primarily through neurokinin-1 (NK-1) receptors of inflammatory and endothelial cells, and may: induce production of reactive oxygen and nitrogen species (superoxide anion, NO•, peroxynitrite, hydroxyl radical), leading to enhanced consumption of tissue antioxidants; stimulate release of inflammatory mediators; promote tissue adhesion molecule expression; and enhance inflammatory cell tissue infiltration and cardiovascular lesion formation. These SP-mediated events may predispose the heart to injury if faced with subsequent oxidative stressors (ischemia/reperfusion, certain drugs) or facilitate development of in situ cardiac dysfunction, especially with prolonged dietary Mg-restriction. Significant protection against most of these MgD-mediated events has been observed with interventions that modulate neuronal SP release or its bioactivity, and with several antioxidants (vitamin E, probucol, epicaptopril, d-propranolol). In view of the clinical prevalence of hypomagnesemia, new treatments, beyond magnesium repletion, may be needed to diminish deleterious neurogenic and prooxidative components described in this article.